PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA BANK ISLAM DI INDONESIA - Hanifah Hanifah; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The purposive of this research is to assess the measurement of the Corporate Governance quality of Islamic Banks and its effect on financial performance. The dependent variable is financial performance that consists of return on asset (ROA) and return on equity (ROE). while the independent variables are the effectiveness of Board of Commissioner, the effectiveness of Audit Commite, and the effectiveness of Shariah Supervisory Board. This research uses multiple regression analysis method with secondary data obtained by purposive sampling method. Research data is secondary data from financial statements and annual reports of Islamic Banks in Indonesia from 2009-2018.The results of this reasearch is indicate there’s a relation between corporate governance and financial performance.